Integrating environment and economy : strategies for local and regional government - Gouldson, Andrew; Roberts, Peter W. (Routledge, 2002)
Integrating Environment and Economy provides a detailed and accessible examination of the policies and practices associated with local and regional strategies for integrating economic development and environmental management.